Anxiety, stress and sleep quality associated to COVID-19 in university students in northwestern Mexico: - Bautista Jacobo, Alejandrina; Quintana Zavala, Maria Olga; Vázquez Bautista, Manuel Alejandro; González Lomelí , Daniel (Horizonte Sanitario, 2023)
Objective: Identify the levels of anxiety, perceived stress, and sleep quality in university students in northwestern Mexico during the COVID-19 pandemic and examine their association to sociodemographic variables and questions related to COVID-19. Materials and methods: Descriptive, correlational, cross-sectional study in a non-probabilistic sample of 1691 students. Online surveys were administered using Google Forms. The chi-square test (χ2), Spearman’s correlation and multivariate logistic regression analysis were used, with the approval of the ethics committee and informed consent of the participants. Results: 38.4% of the students presented moderate anxiety and 36.5% severe anxiety. Moderate level of stress (50.1%) and poor sleep quality (65.8%) predominated. The sex variable was associated to anxiety (χ2 = 88.87, p < .001), perceived stress (χ2 = 72.34, p < .001) and poor sleep quality (χ2 = 31.26, p < .001). Logistic regression determined that students whose family income decreased because of the pandemic were at higher risk of experiencing anxiety (OR = 1.67, p =.001), stress (OR= 1.57, p =.011), and poor sleep quality (OR = 1.46). Conclusions: More than half of the university students who participated in this study presented some level of anxiety, stress and poor sleep quality during the COVID-19 pandemic. Therefore, the development of psychosocial mental health intervention programs aimed at university students is required. Key words: Anxiety; Stress, Psychological; Students.